Early childhood learning analytics: A case study of Learning Jungle - Liang, Rui; Zhu, Hongmei; Lawson, Grant; Lian, Zhao; Huang, Yuqi; Chen, Shengyuan (Frontiers in Applied Mathematics and Statistics, 2023)
The benefits of participating in high-quality Early Childhood Education (ECE) have been recognized by people for many years; and the need for high-quality ECE has never been greater. In this case study, we focus on whether ECE can improve learning speed in five domains: social, emotional, communication, cognition, and physical development. The initial ages for each of these five domains, in months since birth, are collected and compared with that of common children as described in Nipissing District Developmental Screen (NDDS). We find that children in the ECE program learned faster with a p-value no >0.0078. In addition, students in an ECE program are labeled by their ages at enrollment as Cohort 1 (infant) and Cohort 2 (toddler), and we conduct the following statistical tests on their difference: Welch's t-test, Hoteling's T2-test, and survival analysis. We find that the average initial observation age of Cohort 1 is 4.82 months earlier than that of Cohort 2 with a p-value no >0.009. We are convinced that ECE programs could advance students' learning in all five domains.